The backward bending Phillips curves: competing micro-foundations and the role of conflict - Palley, Thomas I. (Investigación Económica, 2019)
The Phillips curve is a critical part of macroeconomics, yet the theoretical foundations of this important relation remain poorly understood. The current paper excavates the micro-foundations of Phillips curve theory, focusing on the competing theoretical explanations of the Phillips curve that adopt a demand-pull perspective. The paper develops a taxonomy of the different theoretical approaches to the Phillips curve, and then presents a simple model of the backward bending Phillips curve that incorporates elements of wage conflict. The model therefore joins together the logic of both the conflict and demand-pull approaches to the Phillips curve, which in the past have been kept separate.